Flame-retardant PC / ABS (polycarbonate / acrylonitrile butadiene styrene) composite material for automobile and preparation process thereof

By hyperbranching modification of the concave and convex rock stone and combining the synergistic effect of antioxidant flame retardants, the shortcomings of existing PC/ABS composites in flame retardant, antistatic and oxidative properties have been solved, and its performance and safety in automotive applications have been significantly improved.

CN119842205AInactive Publication Date: 2025-04-18CHANGZHOU HANYANG POLYMER MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510115949.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PC/ABS composites have shortcomings in flame retardant properties, antistatic properties and oxidation resistance, resulting in safety hazards and aesthetic problems in automotive applications.

Method used

By hyperbranching modification of the concave and concave rock stone, it enhances its dispersion and performance in the PC/ABS mixed resin, and combined with the synergistic effect of antioxidant flame retardant, compatibilizer and toughener, a PC/ABS composite material with excellent flame retardant, antistatic and oxidative properties was prepared.

Benefits of technology

It significantly enhances the flame retardant properties, antistatic properties and oxidation resistance of PC/ABS composites, and improves its safety and durability in automotive trim applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a flame-retardant PC / ABS (polycarbonate / acrylonitrile butadiene styrene) composite material for automobiles and a preparation process thereof, and relates to the technical field of PC / ABS composite materials. The PC / ABS composite material is prepared from the following components in parts by weight: 60 to 70 parts of PC resin, 50 to 60 parts of ABS resin, 6 to 12 parts of hyperbranched modified ATP (Adenosine Triphosphate), 4 to 8 parts of antioxidant flame retardant, 2 to 4 parts of compatilizer and 2 to 4 parts of flexibilizer. Under the synergistic effect of the hyperbranched modified ATP, the antioxidant flame retardant, the compatilizer and the toughening agent, the PC / ABS composite material with excellent flame retardant property, antistatic property and aging resistance is comprehensively prepared, and can be well applied to automobile ornaments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PC / ABS composite materials, in particular to a flame-retardant PC / ABS composite material for automobiles and a preparation process thereof. Background Art

[0002] As automobiles gradually develop towards lightweight and new energy vehicle industry policies are introduced, automotive plastics show a trend of lightweight, environmentally friendly and functional development. The requirements for the multifunctionality of plastics in the automotive, electronic and electrical fields are constantly increasing. The industry trend of lightweight, thin and highly integrated requires that materials must not only have good mechanical properties, processing properties and heat resistance, but also must have excellent flame retardant properties.

[0003] Since PC / ABS composites have good strength, toughness and processing performance, they have gradually become an ideal material for automotive interior and exterior trims. However, conventional PC / ABS composites also have the following problems: (1) poor flame retardancy; (2) poor antistatic performance; (3) poor antioxidant performance. First of all, flame retardancy is the top priority in the development of existing PC / ABS composites and is an extremely important direction for improvement; secondly, a lot of static electricity is often generated inside the car, which in turn leads to dust adsorption and affects the beauty of the interior environment. Therefore, the antistatic performance of PC / ABS composites should also be taken seriously, which is related to the direct experience of customers and affects the sales of cars to a certain extent; finally, the antioxidant performance of common PC resins and ABS resins is poor, and the antioxidant performance of their composites is naturally poor. After a period of oxidation, traditional PC / ABS composites will age and yellow the automotive trims, which will undoubtedly affect customers' purchasing sentiment.

[0004] In summary, in order to solve the above problems, a flame retardant PC / ABS composite material for automobiles was prepared, and its antistatic and antioxidant properties were enhanced and improved to a certain extent. Summary of the invention

[0005] The object of the present invention is to provide a flame retardant PC / ABS composite material for automobiles and a preparation process thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A flame-retardant PC / ABS composite material for automobiles comprises the following components: by weight, 60-70 parts of PC resin, 50-60 parts of ABS resin, 6-12 parts of hyperbranched modified ATP, 4-8 parts of antioxidant flame retardant, 2-4 parts of compatibilizer, and 2-4 parts of toughening agent.

[0007] Furthermore, the PC resin has a melt index of 70-85 g / 10 min at 300° C. and a load of 1.2 kg.

[0008] Furthermore, the melt index of the ABS resin at 220° C. and a load of 10 kg is 65 to 75 g / 10 min.

[0009] Furthermore, the preparation method of the hyperbranched modified ATP is as follows: (1) adding attapulgite and alkenyl silane coupling agent to a 70wt% ethanol aqueous solution, stirring and heating to 50-70°C, stirring and mixing for 3-12h, terminating the reaction, filtering, washing, and drying to obtain alkenyl attapulgite; (2) under a nitrogen atmosphere, adding alkenyl attapulgite, acrylamide, acrylic acid, 2-hydroxyethyl methacrylate phosphate, and 2-acrylamido-2-methylpropanesulfonic acid to anhydrous ethanol, stirring and heating to 65-75°C, adding azobisisobutyronitrile, reflux reaction for 3-12h, terminating the reaction, cooling to room temperature, and adding 10wt% sodium hydroxide solution to the reaction system, adjusting the pH value to 8±0.5, filtering, washing, and drying to obtain hyperbranched modified ATP.

[0010] Furthermore, the mass ratio of the attapulgite to the vinyl silane coupling agent is 1:(0.01~0.1).

[0011] Furthermore, the alkenyl silane coupling agent includes but is not limited to a combination of one or more of vinyl dimethoxy silane, vinyl diethoxy silane, allyl dimethoxy silane, allyl diethoxy silane, 3-butenyl dimethoxy silane, 3-butenyl diethoxy silane, 5-hexenyl dimethoxy silane, and 5-hexenyl diethoxy silane.

[0012] Furthermore, the raw materials required for preparing the hyperbranched modified ATP include the following components: by weight, 15 parts of alkenyl attapulgite, 1 to 3 parts of acrylamide, 3 to 5 parts of acrylic acid, 2 to 4 parts of methacrylic acid-2-hydroxyethyl phosphate, 2 to 4 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.15 to 0.2 parts of azobisisobutyronitrile, and 60 parts of anhydrous ethanol.

[0013] Attapulgite (ATP) has the properties of reinforcement and flame retardancy, and can be added to PC / ABS mixed resin as a filler, which can not only enhance the mechanical properties of PC / ABS composite materials, but also improve the flame retardancy of PC / ABS composite materials. However, if attapulgite is directly added to PC / ABS mixed resin, the prepared PC / ABS composite materials cannot achieve effective improvement in related properties due to the poor dispersibility of attapulgite in the resin solution, and even cause the processing performance and mechanical properties of PC / ABS composite materials to decrease. Therefore, in the present invention, the attapulgite is hyperbranched and modified, firstly modified by an alkenyl silane coupling agent, a carbon-carbon double bond structure is introduced on the surface of the attapulgite, and then free radical initiated polymerization is carried out with acrylamide, acrylic acid, methacrylic acid-2-hydroxyethyl phosphate, and 2-acrylamido-2-methylpropanesulfonic acid, multiple long branches are grafted on the surface of the attapulgite, and finally treated with alkali to obtain hyperbranched modified ATP; the long branches of the hyperbranched modified ATP contain amide groups, hydroxyethyl esters, phosphate groups, sulfonate structures, etc. Among them, the amide group can provide abundant nitrogen elements, and the phosphate group can provide abundant phosphorus elements. Under the synergistic effect of nitrogen and phosphorus, the flame retardant properties of attapulgite can be enhanced; in addition, the hydroxyethyl ester and sulfonate structures can enhance the antistatic properties of attapulgite; at the same time, the hyperbranched modified attapulgite has good compatibility with the PC / ABS mixed resin, which enhances the dispersibility of attapulgite, and because the attapulgite contains multiple branched structures, it can be entangled with the PC resin and the ABS resin, and then an organic-inorganic hybrid network system is constructed, which greatly improves the complexity of the PC / ABS composite material and has a significant improvement on the mechanical properties of the PC / ABS composite material. However, it is also necessary to consider that the internal entanglement of the PC / ABS composite material is too complicated, which will also affect the processing performance of the PC / ABS composite material. Therefore, in the present invention, the degree of hyperbranched modification of attapulgite can be controlled, and the entanglement density of the branch chain and the resin can be further controlled by controlling the number of branch chains, so as to comprehensively consider the processing performance and mechanical properties of the PC / ABS composite material.

[0014] In summary, hyperbranched modified ATP has good dispersion performance in PC / ABS composites and can significantly enhance the flame retardant and antistatic properties of PC / ABS composites.

[0015] Furthermore, the preparation method of the antioxidant flame retardant is as follows: (1) adding maleic anhydride grafted ABS to dimethylformamide, stirring and dissolving, to obtain a maleic anhydride grafted ABS solution; adding DOPO to the maleic anhydride grafted ABS solution, stirring and heating to 140-150°C, reflux reaction for 3-9 hours, ending the reaction, removing dimethylformamide by reduced pressure distillation, washing, and drying to obtain DOPO-terminated maleic anhydride grafted ABS; (2) under a nitrogen atmosphere, adding DOPO-terminated maleic anhydride grafted ABS and polyetheramine to dimethylformamide, stirring and mixing, and placing at 25-5 In a water bath at 0°C, the reaction was stirred for 12 to 36 hours, the reaction was terminated, dimethylformamide was removed by vacuum distillation, the mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine; (3) In a nitrogen atmosphere, DOPO-terminated maleic anhydride grafted ABS-polyetheramine, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid and dicyclohexylcarbodiimide were added to dimethylformamide, the mixture was stirred and mixed, and the mixture was placed in a water bath at 0 to 10°C, the reaction was stirred for 6 to 24 hours, the reaction was terminated, dimethylformamide was removed by vacuum distillation, the mixture was washed and dried to obtain an antioxidant flame retardant.

[0016] Furthermore, the raw materials required for preparing the DOPO-terminated maleic anhydride-grafted ABS include the following components: 15 parts of maleic anhydride-grafted ABS, 1-2 parts of DOPO, and 50 parts of dimethylformamide, by weight.

[0017] Furthermore, the grafting rate of the maleic anhydride grafted ABS is 1-3%.

[0018] Furthermore, the raw materials required for preparing the DOPO-terminated maleic anhydride grafted ABS-polyetheramine include the following components: 12 parts of DOPO-terminated maleic anhydride grafted ABS, 0.5-2 parts of polyetheramine, and 50 parts of dimethylformamide, by weight.

[0019] Furthermore, the polyetheramine is polyetheramine T 403.

[0020] Furthermore, the raw materials required for preparing the antioxidant flame retardant include the following components: by weight, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.3-0.6 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, 0.15-0.3 parts of dicyclohexylcarbodiimide, and 50 parts of dimethylformamide; wherein the dicyclohexylcarbodiimide is a catalyst.

[0021] In the present invention, active hydrogen on DOPO is used to react with double bonds on maleic anhydride grafted ABS to obtain DOPO-terminated maleic anhydride grafted ABS; amino-terminated polyetheramine is then added to undergo amidation grafting with the anhydride on the DOPO-terminated maleic anhydride grafted ABS to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine; finally, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is added. The substance contains a carboxyl group and can undergo amidation reaction with the unreacted amino group on the DOPO-terminated maleic anhydride grafted ABS-polyetheramine to finally prepare an antioxidant flame retardant; wherein in the preparation of the DOPO-terminated maleic anhydride grafted ABS-polyetheramine, the amount of polyetheramine added needs to be controlled so that the anhydride cannot completely react with the amino group on the polyetheramine, and then the next reaction operation can be carried out, so the amount of polyetheramine can be appropriately increased. The prepared antioxidant flame retardant contains DOPO flame retardant structure, maleic anhydride grafted ABS chain end, polyether amine chain end and hindered phenol antioxidant structure; wherein the DOPO flame retardant structure can effectively improve the flame retardant property of PC / ABS composite material; maleic anhydride grafted ABS chain end can promote the good compatibility of antioxidant flame retardant with PC resin and ABS resin, and then be well dispersed in the mixed resin, so as to achieve effective improvement of PC / ABS composite material; ether bond is introduced into the polyether amine chain end, so as to enhance the antistatic property of PC / ABS composite material; hindered phenol antioxidant structure plays a role in improving the defects of poor antioxidant property and easy aging of PC / ABS composite material.

[0022] In summary, since the antioxidant flame retardant has good compatibility with the PC / ABS composite material, the flame retardant, antistatic and antioxidant properties of the PC / ABS composite material can be comprehensively enhanced by adding the antioxidant flame retardant, thereby achieving comprehensive modification of the PC / ABS composite material.

[0023] Furthermore, the compatibilizer is obtained by mixing maleic anhydride grafted ABS and maleic anhydride grafted styrene in a mass ratio of (1-3):1.

[0024] Furthermore, the toughening agent is one or a combination of MBS toughening agent and EMA toughening agent.

[0025] Furthermore, the preparation process of the flame-retardant PC / ABS composite material for automobiles comprises the following steps: S1: weighing raw materials according to the formula ratio, and stirring and mixing to obtain a mixed material; S2: adding the mixed material into a twin-screw extruder, and performing melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material.

[0026] Furthermore, the twin-screw extruder has six sections, the temperature of the first section to the second section is controlled at 200-235°C, and the temperature of the third section to the sixth section is controlled at 240-260°C; the screw speed is 280-350r / min.

[0027] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) In the present invention, the hyperbranched modification of attapulgite enhances the dispersibility of attapulgite in PC / ABS mixed resin, and enhances its flame retardant and antistatic properties, thereby achieving a strong enhancement of the flame retardant and antistatic properties of the PC / ABS composite material; (2) Attapulgite itself can also improve the mechanical properties of PC / ABS composites. After hyperbranching modification, the multi-branched structure can be entangled with the PC / ABS mixed resin to form an organic-inorganic hybrid network structure, thereby increasing the complexity of the PC / ABS composite and improving the processing performance and mechanical properties of the PC / ABS composite. (3) The present invention introduces DOPO flame retardant structure, hindered phenol antioxidant structure and polyetheramine chain end into maleic anhydride grafted ABS to prepare an antioxidant flame retardant; the antioxidant flame retardant can improve the flame retardant properties, anti-aging properties and antistatic properties of PC / ABS composite materials; (4) A PC / ABS composite material with excellent raw material compatibility was prepared by adding hyperbranched modified ATP, antioxidant flame retardant, compatibilizer and toughening agent under the synergistic effect.

[0028] In summary, the present invention prepares a PC / ABS composite material with excellent flame retardant properties, and the PC / ABS composite material also has excellent antioxidant and antistatic properties, and can be well applied in automotive accessories. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] It should be noted that the following parts are calculated by weight, and the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively: The PC resin has a melt index of 70-85 g / 10 min at 300 ° C and a load of 1.2 kg, which was purchased from Jinan City Zhangqiu District Shunbang New Materials Co., Ltd. The ABS resin has a melt index of 65-75 g / 10 min at 220 ° C and a load of 10 kg, which was purchased from Jinan City Zhangqiu District Shunbang New Materials Co., Ltd. The purity of attapulgite is 98%, item number: M62688, purchased from Shanghai Myrel Biochemical Technology Co., Ltd.; The purity of maleic anhydride grafted ABS is 99.8%, the grafting rate is 1.5~2%, model: XYJ1258, purchased from Dongguan Xingyuan Chemical Co., Ltd.; 2-Acrylamido-2-methylpropanesulfonic acid with a purity of 99.5%, CAS number: 15214-89-8, item number: 15214-89-8, 2-hydroxyethyl methacrylate phosphate with a purity of 99.5%, CAS number: 52628-03-2, item number: 52628-03-2, DOPO with a purity of 99.5%, polyetheramine T 403 with a purity of 99.5%, item number: 39423-51-3, all purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.; β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid with a purity of 98%, product number: D808548, purchased from MacLean Biochemical Technology Co., Ltd.; MBS toughening agent, model: EM500, item number: 89, purchased from Foshan Ruisheng Plastic Co., Ltd.; EMA toughening agent, model: 29MA03, item number: 88888, purchased from Dongguan Bailing New Materials Co., Ltd.; Maleic anhydride grafted styrene, item number: 5541254, grafting rate 1%, purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.; other raw materials were purchased from the market; 100 g each.

[0031] Pre-preparation: Compatibilizer: Maleic anhydride grafted ABS and maleic anhydride grafted styrene are uniformly mixed in a mass ratio of 2:1 to obtain a compatibilizer; Toughening agent: MBS toughening agent and EMA toughening agent are uniformly mixed in a mass ratio of 1:1 to obtain a toughening agent.

[0032] Example 1: Preparation process of a flame retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 0.9 parts of vinyl diethoxysilane to a 70 wt% ethanol aqueous solution, stir and heat to 60°C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 2 parts of acrylamide, 4 parts of acrylic acid, 3 parts of methacrylic acid-2-hydroxyethyl phosphate, and 3 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70°C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt% sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 1.5 parts of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 1.5 parts of polyetheramine T 403 was added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 40°C for 24 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine. (3) Under a nitrogen atmosphere, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.45 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.23 parts of dicyclohexylcarbodiimide were added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 0°C for 18 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain an antioxidant flame retardant. S13. The raw materials were weighed in weight proportions of 65 parts of PC resin, 55 parts of ABS resin, 9 parts of hyperbranched modified ATP, 6 parts of antioxidant flame retardant, 3 parts of compatibilizer and 3 parts of toughening agent, and placed in a mixer and mixed to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0033] Example 2: Preparation process of a flame retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 0.15 parts of vinyl diethoxysilane to a 70 wt % ethanol aqueous solution, stir and heat to 60 ° C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 1 part of acrylamide, 3 parts of acrylic acid, 2 parts of methacrylic acid-2-hydroxyethyl phosphate, and 2 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70 ° C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt % sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 1 part of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 0.5 parts of polyetheramine T403 to 50 parts of dimethylformamide, stir and mix, and place at 4 In a water bath at 0°C, the reaction was stirred for 24 hours, the reaction was terminated, dimethylformamide was removed by vacuum distillation, the mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine; (3) In a nitrogen atmosphere, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.15 parts of dicyclohexylcarbodiimide were added to 50 parts of dimethylformamide, the mixture was stirred, and the mixture was placed in a water bath at 0°C, the reaction was stirred for 18 hours, the reaction was terminated, dimethylformamide was removed by vacuum distillation, the mixture was washed and dried to obtain an antioxidant flame retardant; S13. The raw materials were weighed in weight ratio of 65 parts of PC resin, 55 parts of ABS resin, 6 parts of hyperbranched modified ATP, 4 parts of antioxidant flame retardant, 2 parts of compatibilizer and 2 parts of toughening agent, and placed in a mixer and mixed to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0034] Example 3: Preparation process of a flame retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 1.5 parts of vinyl diethoxysilane to a 70 wt % ethanol aqueous solution, stir and heat to 60 ° C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 3 parts of acrylamide, 5 parts of acrylic acid, 4 parts of methacrylic acid-2-hydroxyethyl phosphate, and 4 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70 ° C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt % sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 2 parts of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 2 parts of polyetheramine T403 to 50 parts of dimethylformamide, stir and mix, and place at 40 ℃ water bath environment, stirring the reaction for 24 hours, ending the reaction, removing dimethylformamide by vacuum distillation, washing and drying to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine; (3) Under a nitrogen atmosphere, add 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.6 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.3 parts of dicyclohexylcarbodiimide to 50 parts of dimethylformamide, stir to mix, and place in a 0℃ water bath environment, stirring the reaction for 18 hours, ending the reaction, removing dimethylformamide by vacuum distillation, washing and drying to obtain an antioxidant flame retardant; S13. The raw materials were weighed in weight ratio of 65 parts of PC resin, 55 parts of ABS resin, 12 parts of hyperbranched modified ATP, 8 parts of antioxidant flame retardant, 4 parts of compatibilizer and 4 parts of toughening agent, and placed in a mixer and mixed to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0035] Based on Example 1, a control experiment is carried out below, and comparative examples 1 to 5 are set in sequence, as follows: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: ATP is not modified, and other processes remain unchanged, specifically: A preparation process of flame-retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 1.5 parts of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 1.5 parts of polyetheramine T 403 was added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 40°C for 24 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine. (3) Under a nitrogen atmosphere, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.45 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.23 parts of dicyclohexylcarbodiimide were added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 0°C for 18 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain an antioxidant flame retardant. S12. The raw materials were weighed in weight proportions of 65 parts of PC resin, 55 parts of ABS resin, 9 parts of ATP, 6 parts of antioxidant flame retardant, 3 parts of compatibilizer and 3 parts of toughening agent, and mixed evenly in a mixer to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0036] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following modifications: DOPO, polyetheramine, and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid are directly added as raw material components into the twin-screw extruder, and other processes remain unchanged, specifically: A preparation process of flame-retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 0.9 parts of vinyl diethoxysilane to a 70 wt% ethanol aqueous solution, stir and heat to 60°C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 2 parts of acrylamide, 4 parts of acrylic acid, 3 parts of methacrylic acid-2-hydroxyethyl phosphate, and 3 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70°C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt% sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. Weigh the raw materials according to the weight ratio of 65 parts of PC resin, 55 parts of ABS resin, 9 parts of hyperbranched modified ATP, 1.5 parts of DOPO, 1.5 parts of polyetheramine T403, 0.45 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3 parts of compatibilizer, and 3 parts of toughening agent, and mix them in a mixer to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0037] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following modifications: no hyperbranched modified ATP is added, and other processes remain unchanged, specifically: A preparation process of flame-retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 1.5 parts of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 1.5 parts of polyetheramine T 403 was added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 40°C for 24 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine. (3) Under a nitrogen atmosphere, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.45 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.23 parts of dicyclohexylcarbodiimide were added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 0°C for 18 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain an antioxidant flame retardant. S12. The raw materials were weighed in weight ratios of 65 parts PC resin, 55 parts ABS resin, 6 parts antioxidant flame retardant, 3 parts compatibilizer and 3 parts toughening agent, and mixed evenly in a mixer to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0038] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: no antioxidant flame retardant is added, and other processes remain unchanged, specifically: A preparation process of flame-retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 0.9 parts of vinyl diethoxysilane to a 70 wt% ethanol aqueous solution, stir and heat to 60°C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 2 parts of acrylamide, 4 parts of acrylic acid, 3 parts of methacrylic acid-2-hydroxyethyl phosphate, and 3 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70°C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt% sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. The raw materials were weighed in weight ratio of 65 parts of PC resin, 55 parts of ABS resin, 9 parts of hyperbranched modified ATP, 3 parts of compatibilizer and 3 parts of toughening agent, and mixed evenly in a mixer to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0039] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustments: no compatibilizer and toughening agent are added, and other processes remain unchanged, specifically: A preparation process of flame-retardant PC / ABS composite material for automobiles: S1: Raw material preparation: S11. Preparation of hyperbranched modified ATP: (1) Add 15 parts of attapulgite and 0.9 parts of vinyl diethoxysilane to a 70 wt% ethanol aqueous solution, stir and heat to 60°C, stir and mix for 9 hours, terminate the reaction, filter, wash and dry to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add 15 parts of alkenyl attapulgite, 2 parts of acrylamide, 4 parts of acrylic acid, 3 parts of methacrylic acid-2-hydroxyethyl phosphate, and 3 parts of 2-acrylamido-2-methylpropanesulfonic acid to 60 parts of anhydrous ethanol, stir and heat to 70°C, then add 0.2 parts of azobisisobutyronitrile, reflux for 9 hours, terminate the reaction, cool to room temperature, add 10 wt% sodium hydroxide solution to the reaction system, adjust the pH value to 8, filter, wash and dry to obtain hyperbranched modified ATP; S12. Preparation of antioxidant flame retardant: (1) Add 15 parts of maleic anhydride grafted ABS to 50 parts of dimethylformamide, stir and dissolve to obtain maleic anhydride grafted ABS solution; add 1.5 parts of DOPO to the maleic anhydride grafted ABS solution, stir and heat to 145°C, reflux for 6 hours, terminate the reaction, remove dimethylformamide by vacuum distillation, wash and dry to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, add 12 parts of DOPO-terminated maleic anhydride grafted ABS and 1.5 parts of polyetheramine T 403 was added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 40°C for 24 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine. (3) Under a nitrogen atmosphere, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.45 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, and 0.23 parts of dicyclohexylcarbodiimide were added to 50 parts of dimethylformamide, stirred and mixed, and placed in a water bath at 0°C for 18 hours of stirring reaction. The reaction was terminated, and the dimethylformamide was removed by vacuum distillation. The mixture was washed and dried to obtain an antioxidant flame retardant. S13. The raw materials were weighed in weight ratio of 65 parts of PC resin, 55 parts of ABS resin, 9 parts of hyperbranched modified ATP and 6 parts of antioxidant flame retardant, and mixed evenly in a mixer to obtain a mixed material; S2: Preparation of flame retardant PC / ABS composite materials: The mixed material is added into a twin-screw extruder, and subjected to melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material; the twin-screw extruder has six sections, and the controlled temperatures of the six sections are 220°C, 235°C, 255°C, 255°C, 255°C, and 240°C respectively, and the screw speed is 300r / min.

[0040] Performance test: According to the relevant standards, the flame retardant PC / ABS composite materials prepared in the examples and comparative examples were injection molded into test specimens, and the following tests were performed respectively: (1) Flame retardant performance: Flame retardant performance test according to UL94 standard; (2) Antistatic performance: The surface resistivity of the sample is tested to evaluate the antistatic performance; (3) Mechanical properties: According to the standard of GB / T 1040, the tensile properties test was carried out and the tensile strength was used to characterize its mechanical properties; (4) Antioxidant properties: The test specimens were irradiated with UVA340Lamp for 72 hours, and then subjected to mechanical property tests. The specific data results of the above tests are shown in Table 1 below: Table 1

[0041] Result analysis: By comparing the data of the embodiment and comparative examples 1 and 3 in Table 1 above, it can be seen that the hyperbranched modified ATP prepared by the present invention can well enhance the flame retardancy, antistatic properties and mechanical properties of the PC / ABS composite material; by comparing the data of the embodiment and comparative example 2, it can be seen that the antioxidant flame retardant prepared by the present invention has excellent compatibility with the PC / ABS mixed resin, and can better improve the flame retardancy, antioxidant properties and antistatic properties of the PC / ABS composite material; by comparing the embodiment and comparative example 5, it can be seen that the compatibilizer and toughening agent in the present invention also have a great influence on the relevant properties of the PC / ABS composite material, and they, together with the hyperbranched modified ATP and the antioxidant flame retardant, enhance and improve the PC / ABS composite material.

[0042] In summary, under the synergistic effect of hyperbranched modified ATP, antioxidant flame retardant, compatibilizer and toughening agent, the present invention prepares a high-performance PC / ABS composite material with excellent flame retardant properties, antistatic properties, antioxidant properties and mechanical properties.

[0043] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A flame retardant PC / ABS composite material for automobiles, characterized in that: The invention comprises the following components: by weight, 60-70 parts of PC resin, 50-60 parts of ABS resin, 6-12 parts of hyperbranched modified ATP, 4-8 parts of antioxidant flame retardant, 2-4 parts of compatibilizer and 2-4 parts of toughening agent.

2. The flame retardant PC / ABS composite material for automobiles according to claim 1, characterized in that: The preparation method of the hyperbranched modified ATP is: (1) adding attapulgite and an alkenyl silane coupling agent to a 70 wt% ethanol aqueous solution, stirring and heating to 50-70° C., stirring and mixing for 3-12 hours, ending the reaction, filtering, washing, and drying to obtain alkenyl attapulgite; (2) Under a nitrogen atmosphere, add alkenyl attapulgite, acrylamide, acrylic acid, 2-hydroxyethyl methacrylate phosphate, and 2-acrylamido-2-methylpropanesulfonic acid to anhydrous ethanol, stir and heat to 65-75°C, then add azobisisobutyronitrile, reflux for 3-12 hours, terminate the reaction, cool to room temperature, add 10 wt% sodium hydroxide solution to the reaction system, adjust the pH to 8±0.5, filter, wash, and dry to obtain hyperbranched modified ATP.

3. The flame retardant PC / ABS composite material for automobiles according to claim 2, characterized in that: The mass ratio of the attapulgite and the alkenyl silane coupling agent is 1:(0.01-0.1); the raw materials required for the preparation of the hyperbranched modified ATP, The invention comprises the following components: by weight, 15 parts of alkenyl attapulgite, 1-3 parts of acrylamide, 3-5 parts of acrylic acid, 2-4 parts of methacrylate-2-hydroxyethyl phosphate, 2-4 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.15-0.2 parts of azobisisobutyronitrile and 60 parts of anhydrous ethanol.

4. The flame retardant PC / ABS composite material for automobiles according to claim 2, characterized in that: The alkenyl silane coupling agent includes one or more combinations of vinyl dimethoxy silane, vinyl diethoxy silane, allyl dimethoxy silane, allyl diethoxy silane, 3-butenyl dimethoxy silane, 3-butenyl diethoxy silane, 5-hexenyl dimethoxy silane, and 5-hexenyl diethoxy silane.

5. The flame retardant PC / ABS composite material for automobiles according to claim 1, characterized in that: The preparation method of the antioxidant flame retardant is: (1) Adding maleic anhydride grafted ABS to dimethylformamide, stirring and dissolving, to obtain a maleic anhydride grafted ABS solution; adding DOPO to the maleic anhydride grafted ABS solution, stirring and heating to 140-150°C, reflux reaction for 3-9 hours, ending the reaction, removing dimethylformamide by vacuum distillation, washing and drying, to obtain DOPO-terminated maleic anhydride grafted ABS; (2) Under nitrogen atmosphere, DOPO-terminated maleic anhydride grafted ABS and polyetheramine are added to dimethylformamide, stirred and mixed, and placed in a water bath at 25-50°C, stirred and reacted for 12-36 hours, and then the reaction was terminated. The dimethylformamide was removed by vacuum distillation, and the mixture was washed and dried to obtain DOPO-terminated maleic anhydride grafted ABS-polyetheramine; (3) Under a nitrogen atmosphere, DOPO-capped maleic anhydride grafted ABS-polyetheramine, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid and dicyclohexylcarbodiimide were added to dimethylformamide, stirred and mixed, and placed in a water bath at 0-10°C for 6-24 hours. After the reaction was terminated, dimethylformamide was removed by vacuum distillation, and the mixture was washed and dried to obtain an antioxidant flame retardant.

6. The flame retardant PC / ABS composite material for automobiles according to claim 5, characterized in that: The raw materials required for preparing the DOPO-terminated maleic anhydride-grafted ABS are The invention comprises the following components: by weight, 15 parts of maleic anhydride grafted ABS, 1-2 parts of DOPO, and 50 parts of dimethylformamide; The DOPO-terminated maleic anhydride grafted ABS-polyetheramine is used to prepare the required raw materials, The invention comprises the following components: by weight, 12 parts of DOPO-terminated maleic anhydride grafted ABS, 0.5-2 parts of polyetheramine, and 50 parts of dimethylformamide; the raw materials required for preparing the antioxidant flame retardant comprise the following components: by weight, 10 parts of DOPO-terminated maleic anhydride grafted ABS-polyetheramine, 0.3-0.6 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid, 0.15-0.3 parts of dicyclohexylcarbodiimide, and 50 parts of dimethylformamide.

7. The flame retardant PC / ABS composite material for automobiles according to claim 5, characterized in that: The grafting rate of the maleic anhydride grafted ABS is 1-3%; and the polyetheramine is polyetheramine T 403.

8. The flame retardant PC / ABS composite material for automobiles according to claim 1, characterized in that: The compatibilizer is obtained by mixing maleic anhydride grafted ABS and maleic anhydride grafted styrene in a mass ratio of (1-3):1; the toughening agent is one of MBS toughening agent and EMA toughening agent or a combination of two thereof.

9. A process for preparing a flame-retardant PC / ABS composite material for automobiles according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: weighing raw materials according to the weight ratio of the components described in claim 1, and stirring and mixing to obtain a mixed material; S2: adding the mixed material into a twin-screw extruder, and performing melt extrusion, cooling, and pelletizing to obtain a flame-retardant PC / ABS composite material for automobiles.

10. The process for preparing a flame-retardant PC / ABS composite material for automobiles according to claim 9, characterized in that: The twin-screw extruder has six sections, the temperature of the first section to the second section is controlled at 200-235°C, and the temperature of the third section to the sixth section is controlled at 240-260°C; the screw speed is 280-350r / min.

Citation Information

Patent Citations

  • Halogen-free flame retardant antistatic PC / ABS alloy material and preparation method thereof

    CN102585469A

  • Antistatic antibacterial PC (polycarbonate) / ABS (acrylonitrile-butadiene-styrene copolymer) composite material

    CN104513469A

  • Antistatic, low-smoke, halogen-free and flame-retardant PC / ABS blend material and preparation method thereof

    CN111117183A

  • PC / ABS composite material and preparation method thereof

    CN111234499A

  • PC / ABS anti-aging automobile special material and preparation method thereof

    CN112940478A

Cited By

  • High-performance flame-retardant ABS composite material and preparation method thereof

    CN120173361A

  • High-performance flame-retardant ABS composite material and preparation method thereof

    CN120173361B

  • Temperature-resistant, flame-retardant and anti-corrosion composite material for building as well as preparation method and application of composite material

    CN120648194A

  • A temperature-resistant, flame-retardant, and corrosion-resistant building composite material, a preparation method and application thereof

    CN120648194B

  • High-durability and flame-retardant building template material, preparation method thereof and building template

    CN120758010A